2015
DOI: 10.1371/journal.pone.0131126
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Status and Its Related Factors in Pregnant Women in Bangkok, Thailand

Abstract: BackgroundThere are few data focusing on the prevalence of vitamin D deficiency in tropical countries. ObjectivesWe determined the vitamin D status in pregnant women and examined the factors associated with vitamin D deficiency. Design and MethodsA cross-sectional study of 147 pregnant Thai women aged 18–45 years at Siriraj Hospital (a university hospital in Bangkok, Thailand) was undertaken. Clinical data and plasma levels of 25-hydroxyvitamin D [25(OH)D], intact parathyroid hormone (iPTH), calcium, albumin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 76 publications
(73 reference statements)
5
26
5
Order By: Relevance
“…To our knowledge this is the first large-scale study on vitamin D status and analysis on associated risk factors for vitamin D deficiency of lactating women in China. The median of serum 25(OH)D was only 15.8 nmol/L which was much lower than that of the cutoff point (30nmol/L) to define vitamin D deficiency and also much lower than the means of lactating women reported previously in US [31], Thailand [30] and United Arab Emirates [32], and similar to those reported in lactating women living in Lahore [7]. Therefore, our results indicated that lactating women would be vulnerable groups suffered from vitamin D deficiency because such populations usually avoid direct exposure to sunlight and consume fewer foods naturally rich in vitamin D and national fortification of food with vitamin D has not been implemented in China.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…To our knowledge this is the first large-scale study on vitamin D status and analysis on associated risk factors for vitamin D deficiency of lactating women in China. The median of serum 25(OH)D was only 15.8 nmol/L which was much lower than that of the cutoff point (30nmol/L) to define vitamin D deficiency and also much lower than the means of lactating women reported previously in US [31], Thailand [30] and United Arab Emirates [32], and similar to those reported in lactating women living in Lahore [7]. Therefore, our results indicated that lactating women would be vulnerable groups suffered from vitamin D deficiency because such populations usually avoid direct exposure to sunlight and consume fewer foods naturally rich in vitamin D and national fortification of food with vitamin D has not been implemented in China.…”
Section: Discussionmentioning
confidence: 63%
“…It has been reported that vitamin D deficiency is a major public health concern worldwide in all age groups particular in special physiological stage such as pregnancy and lactation[29], even in the populations living in those countries with low latitude, where it was generally assumed that UV radiation was adequate to prevent vitamin D deficiency, and in industrialized countries, where vitamin D fortification has been implemented for decades [14, 18, 20, 30]. However, few studies had been conducted in lactating women at national level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations